PENGUATAN BUDAYA ILMIAH MAHASISWA DI STAIN MANDAILING NATAL MELALUI PEMBENTUKAN UKM KARYA ILMIAH DAN PENELITIAN - Zulfahmi Zulfahmi; Maulana Muklis (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
This research aims to analyze the enhancement of the scientific culture among students at the Mandailing Natal State Islamic College (STAIN) through the establishment of a Student Activity Unit (UKM) for Scientific Work and Research. A survey of 180 students across various study programs revealed that over 50% were unable to write scientific papers proficiently. Many students reported struggling with scientific writing techniques and expressed dissatisfaction with the guidance they received. This study employs qualitative methods, including interviews and document analysis, to identify the challenges students face and the role of the UKM in addressing these issues. The findings suggest that the formation of the Scientific Work and Research UKM at STAIN Mandailing Natal could be an effective solution to improving students' writing abilities. The UKM is designed to organize activities such as training sessions, seminars, and scientific writing competitions to foster a scientific culture among students. The study also compares the results with the success of similar UKMs at other universities, which have proven effective in supporting the development of students' scientific writing skills. It is hoped that, through this UKM, STAIN Madina students will be better equipped to meet increasingly complex academic demands and produce high-quality scientific work.